Research Methods - The Key Concepts - Hammond, M.; Wellington, J. (Routledge, 2013)
This invaluable resource provides a comprehensive overview of the many methods and methodologies of social research. Each entry provides a critical definition and examines the value and difficulties of a particular method or methodology of concept across different fields of social research. Concepts include: Action research Chaos theory Discourse analysis Epistemology Literature review Interviewing Social constructivism World view With thematic further reading stretching across the social sciences, Research Methods: The Key Concepts will help readers develop a firm understanding of the rationale and principles behind key research methods, and is a must-have for new researchers at all levels, from undergraduate to postgraduate and beyond.